If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 74 + -22 = 13Y Combine like terms: 74 + -22 = 52 52 = 13Y Solving 52 = 13Y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-13Y' to each side of the equation. 52 + -13Y = 13Y + -13Y Combine like terms: 13Y + -13Y = 0 52 + -13Y = 0 Add '-52' to each side of the equation. 52 + -52 + -13Y = 0 + -52 Combine like terms: 52 + -52 = 0 0 + -13Y = 0 + -52 -13Y = 0 + -52 Combine like terms: 0 + -52 = -52 -13Y = -52 Divide each side by '-13'. Y = 4 Simplifying Y = 4
| 7.92y=2.2x | | .10(x)+.25(y)=12.55 | | 39.95-0.49x=75 | | 8(j-3)=4j+9j+-14 | | 125+55x=400 | | X^2+y^2+2x+4y=20 | | 3y=8x | | -3(2x-4)+8x=20 | | 15y=5x | | y^2-8y+0=0 | | 6(7-10x)+3(3-15x)=336 | | 25-4x=97 | | 10(x)+25(y)=12.55 | | 7-1.5ln*15= | | 5(y+2)-3=y-5+y | | 8C^4/11C^4 | | 3x+2x-1=69 | | (10x-9)=(4x+57) | | 7(x+7)=6(x+6) | | 8m+1=5 | | 5(3x-4)+2x-15=8x+120-3x | | 3*8*9=x | | .08x=.05x+15 | | (-5)+3+18+(-14)= | | 6x+2=3(3+6x) | | (3x-4)+2x-15=8x+120-3x | | a^2-9a-57=-5 | | 1.5ln= | | 8-3k=3k+21 | | log(3)x=log(4)3x | | 9p-4=50+3p | | 3(3-1)+(9)-9= |